Performansi Bahasa Arab dan Pemahaman Keagamaan: Pembentukan Identitas Sosial pada Mahasiswa Kajian Bahasa Arab di Indonesia - Pahlefi, M Riza; Syahid, Ahmad Habibi; Nuroh, Nuroh (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to analyze and explore the role of Arabic language performance in shaping the social identity of Arabic study students at State Islamic Religious Colleges (PTKIN), as well as its relationship with their religious understanding. This study uses a sociolinguistic approach with mixed methods, combining quantitative data from a survey of Arabic study students at several PTKINs, as well as qualitative data from in-depth interviews. The data were analyzed to identify how Arabic is used not only as a means of communication, but also as an expression of religious and cultural identity. The results of the study indicate that Arabic language performance among Arabic study students not only improves their language skills, but also strengthens their social and religious identities as Muslims. Arabic is used significantly as a medium that integrates aspects of religiosity and culture in students' academic and social lives. These findings confirm that Arabic has an important role in maintaining and strengthening religious and cultural identities in Islamic higher education environments. In conclusion, Arabic language performance not only has an impact on language proficiency, but also shapes the social identity and religious understanding of students at PTKINs. This research has significance in enriching sociolinguistic studies in Indonesia and provides implications for Arabic language learning strategies that are more integrated with aspects of religious and social identity in the PTKIN environment, making it a tool for developing a broader cultural understanding and a strong religious identity